PENGENALAN HAK ASASI MANUSIA BAGI SISWA DI PERBATASAN : PENGABDIAN MASYARAKAT DI PULAU SEBATIK - Tobroni, Faiq (Empowerment : Jurnal Pengabdian Masyarakat, 2020)
Human Rights Study does not only serve to introduce the freedom that everyone has. This study is also appropriate to be used as a media to strengthen nationalism. The purpose of service is to provide an understanding of the important role of the state in respecting, protecting and fulfilling human rights, this understanding will strengthen the spirit of love of every citizen of his country (nationalism). Utilizing this relationship, the author innovates service through the introduction of human rights to students in border areas to strengthen their nationalism. This service method is carried out with several activities, namely telling stories, singing and playing guesses related to the theme of human rights. The choice of some of these activities is intended to adjust the service goals, namely elementary school students. Paying attention to the psychology of their age, the introduction of human rights is done in such a way that is in a language that is easily understood by children of primary school age. The result of dedication is that even with simple language and fun techniques, this service has succeeded in introducing human rights to elementary school students while at the same time strengthening their nationalism by connecting the concept of the struggle for human rights with the struggle for Indonesian independence.Keywords: Human Rights, Independence, Nationalism and Students. AbstrakKajian Hak Asasi Manusia (HAM) tidak hanya berfungsi mengenalkan kebebasan yang dimiliki setiap orang. Kajian ini juga layak digunakan sebagai media penguatan nasionalisme. Tujuan pengabdian adalah memberikan pemahaman pentingnya peran negara dalam penghormatan, perlindungan dan pemenuhan HAM, pemahaman ini akan memperkuat semangat kecintaan setiap warga negara kepada negaranya (nasionalisme). Memanfaatkan hubungan tersebut, penulis menginovasi pengabdian melalui pengenalan HAM kepada siswa di wilayah perbatasan untuk memperkuat nasionalisme mereka.  Metode pengabdian ini dilaksanakan dengan beberapa kegiatan, yakni bercerita, bernyanyi dan bermain tebak-tebakan berkaitan dengan tema HAM. Pilihan beberapa kegiatan tersebut dimaksudkan untuk menyesuaikan sasaran pengabdian, yakni siswa sekolah dasar. Memperhatikan psikologi usia mereka, pengenalan HAM dilakukan sedemikian rupa sesuai dengan bahasa yang mudah dipahami oleh anak-anak usia sekolah dasar. Hasil pengabdian yaitu walaupun dngan bahasa yang sederhana dan teknik yang menyenangkan, pegabdian ini berhasil memperkenalkan HAM kepada siswa sekolah dasar sekaligus memmperkuat nasionalisme mereka dengan cara menghubungkan konsep perjuangan HAM dengan perjuangan kemerdekaan Indonesia.Kata Kunci: Hak Asasi Manusia, Kemerdekaan, Nasionalisme dan Siswa.